A Strategic Initiative for Successful Reverse Logistics Management in Retail Industry - Panigrahi, Shrikant; Foo, Weng Kar; Tan, Ai Fen; Lam, Kah Hoe; Melvin, Wong (Sage, 2018)
This study aims to identify critical factors for developing a successful reverse logistics strategic framework that could guide the managers for improving customer satisfaction and managing retail returns. Qualitative interviews were performed with logistics manager in retail industry to develop successful reverse logistics strategic framework with critical factors. A problem-driven content analysis methodology was also conducted reviewing previous studies published from 2008 through 2015 to determine the key factors that affect reverse logistics decisions of managers towards successful reverse logistics management. This study provided new insight on reverse logistics as an important strategic initiative for the retailers to gain customer satisfaction, competitive advantage and cost effectiveness. A reverse logistics framework that is developed in this article will be able to add value to supply chain and logistics studies. Reverse flow driven by motivation is an important implication for managers to manage logistics activities. Managers must emphasize on potential corporate benefits to reduce costs and add customer value.